Evaluation of natural compounds as VEGFR-2 inhibitors for breast cancer therapy: insights from molecular docking and drug-likeness analysis - Aprilia, Vika; Sarmoko; Fareza, Muhamad Salman; Baroroh, Hanif Nasiatul; Choironi, Nur Amalia (Pharmacy Reports, 2024)
Breast cancer remains one of the most common cancers worldwide, with VEGFR-2 (KDR) playing a key role in tumor angiogenesis. Inhibiting VEGFR-2 is a promising therapeutic strategy. Natural compounds are increasingly studied for their potential to inhibit VEGFR-2. This study aims to assess the binding affinity of 11 natural compounds (andrographolide, alpha-mangostin, pinostrobin, pinocembrin, ethyl-p-methoxycinnamate (EPMS), xanthorrhizol, galangin, gamma-mangostin, curcumin, cinnamaldehyde, and alashanoid B) to the VEGFR-2 protein through molecular docking and Lipinski's rule analysis, identifying promising candidates for breast cancer treatment. Molecular docking simulations were performed for 11 compounds and sunitinib as a control, with binding energies and interactions analyzed. The compounds were also evaluated for drug-likeness using Lipinski’s rule of five. Curcumin showed the highest binding affinity to VEGFR-2 with a binding energy of -9.9 kcal/mol, surpassing sunitinib (-9.4 kcal/mol). Key interactions were observed with active site residues Cys919 and Asp1046. All tested compounds met the criteria for oral bioavailability per Lipinski’s rules. Curcumin demonstrates potential as a VEGFR-2 inhibitor due to its favorable binding affinity and drug-like properties. Enhancing curcumin’s bioavailability is recommended for effective therapeutic application.